Relationship between Emotional Intelligence and Systemic Thinking in Nurse Managers: A Correlational Study - Maryam Katebi; Masoud Bahreini; Razieh Bagherzadeh; Shahnaz Pouladi (پیاورد سلامت)
Background and Aim: Nurse managers leverage managerial intelligence to mitigate decision-making challenges and systemic issues. Emotional intelligence, a crucial aspect of managerial intelligence, is vital for job performance and leadership. This skill enables managers to comprehend their emotions and those of others and establish more effective communication. Also, managers in complex environments, such as hospitals, need systemic thinking. Systemic thinking enables managers to solve problems comprehensively, enhancing decision-making accuracy and efficiency. This study was conducted to determine the relationship between emotional intelligence and systemic thinking in nurse managers of affiliated hospitals of Bushehr University of Medical Sciences. Materials and Methods: The present study is a descriptive-analytical correlational study. One hundred and forty-five nurse managers working in Bushehr University of Medical Sciences-affiliated hospitals were included in the study based on the inclusion criteria. The sampling was done as a full census. Data were collected using the demographic information form, Bradbury and Graves’ emotional intelligence questionnaire, and Amini et al.’s systemic thinking questionnaire. Data were analyzed using SPSS software, descriptive statistics (frequency, mean, and standard deviation), and analytical statistics (Pearson correlation coefficient). A significance level of less than 0.05 was considered in all cases. Results: This study involved 145 nurse managers, 88.3% female, 84.8% married, and 87.6% holding a Bachelor of Science in Nursing (BSN). The mean age and average tenure in managerial positions were 41.93±6.37 and 8.68±6.52 years, respectively. The mean score for emotional intelligence (EI) among nurse managers was 130.81±11.84 (range: 28-168), while the mean score for systems thinking (ST) was 43.30±5.90 (range: 8-56). A positive correlation was found between emotional intelligence and systems thinking (r=0.365, P<0.001); however, EI was not a significant predictor of ST (β=0.131, P=0.146). Conclusion: Considering the positive correlation between emotional intelligence and systemic thinking as essential management competencies, it is suggested that training these skills should be considered in continuing education programs for nurses and nurse managers. This will help managers strengthen their emotional intelligence and apply systemic strategies in nursing management.